Atmospheric and Oceanic Processes in the Vicinity of an Island Strait - Julie Pullen; Arnold L. Gordon; Janet Sprintall; Craig M. Lee; James D. Doyle; Paul May (Oceanography, 2011)
In early February 2008, the mean flow through the Philippines’ Mindoro Strait reversed. The flow was southward through the strait during late January and northward during most of February. The flow reversal coincided with the period between two intensive observing cruises (IOP-08-1 and IOP-08-2) sponsored by the Office of Naval Research as part of the Philippines Experiment (PhilEx). Employing high-resolution oceanic and atmospheric models supplemented with in situ ocean and air measurements, we detail the regional and local conditions that influenced this flow reversal. High-resolution air/sea modeling simulations captured the flow reversal and agreed with measured currents from two moorings in the vicinity of Mindoro Strait. A short (January 24–27) easterly monsoon surge and a longer (February 9–16) northerly surge were represented in the model as well as in QuikSCAT and underway wind data taken during IOP-08-2. Mesoscale oceanic dipole eddies off Mindoro and Luzon islands were formed/enhanced and subsequently detached during these wind events. The cyclonic eddy in the dipole pair associated with the easterly surge was opportunistically sampled during the IOP-08-1 cruise and the modeled eddy characteristics were verified using in situ shipboard data. The predominant geostrophic southward flow through the strait was interrupted by a strong and sustained wind-driven (by the northerly surge) flow reversal in early February. Enhanced upper-ocean stratification in winter 2008 due to anomalously high precipitation served to isolate the observed near-surface flow.